Efeitos de nitrocomplexo de rutênio (for0777g) na morfofisiologia vascular em aortas isoladas de ratos wistar - Soares, João Junior Faustino (2024)
The vascular endothelium plays a crucial role in regulating vascular tone, balancing the production of vasodilatory and vasoconstrictor substances. Endothelial dysfunction, associated with conditions such as systemic arterial hypertension, can compromise this regulation. Therefore, the development of new nitric oxide (NO) donors, such as ruthenium complexes, gains relevance to treat vascular dysfunctions. In this study, we investigated the effects of ruthenium nitrocomplex (FOR0777G) on the vascular morphophysiology of aortas isolated from Wistar rats. The main objective was to elucidate the mechanisms of action involved in the vasodilatory effect of FOR0777G. To achieve this objective, we examined the vascular response under different experimental conditions, considering the presence or absence of endothelium and the influence of specific inhibitors. Aortic rings from Wistar rats were used, with intact or denuded endothelium, pre-contracted with phenylephrine (PHE) or potassium chloride (KCl). Concentration-effect curves were prepared using FOR0777G. A series of inhibitors/blockers (L-NAME, ODQ, tetraethylammonium, barium chloride, hydroxocobalamin, 4-aminopyridine, glibenclamide, L-cysteine, wortmannin) were used to investigate possible mechanisms of action. The aortic rings were fixed in 10% buffered formalin for 24 to 48 hours. The material was processed normally for histological examination, the slides were stained with hematoxylin and eosin (HE). Comparative analysis between two groups was performed using the t test for unpaired data, while for the comparison of three or more groups, analysis of variance with Tukey's multiple comparison test was used. In reactivity tests, it was possible to verify the vasodilation of FOR0777G, which showed EC50 results of 0.11 μg/mL (95% CI: 0.08 – 0.16) and EMAX was 112.94 ± 1.93% with higher dilation than DMSO 15.461 μg/mL (95% CI: 1.84 – 19.07) and EMAX 12.26 ± 5.62%. It was observed that the vasodilatory action of FOR0777G is not dependent on the endothelium. In preparations with different inhibitors, only hydroxocobalamin and ODQ showed a significant reduction in EMAX, resulting in 94.96 ± 12.11% and 66.37 ± 9.41%. Histological analysis did not reveal any lesions in the tissue of the aortic rings, only a slight disorganization of the muscle fibers in the middle layer, and further study is needed. In this context, FOR0777G can be classified as a potential NO-donating agent and stimulator/activator of the NO-dependent soluble guanylate cyclase pathway and endothelium-independent vasorelaxant effect.